Voting for far-right parties in the 2014 European Parliament Elections - Μαυροπούλου, Ευγενία (Επιστήμη και Κοινωνία: Επιθεώρηση Πολιτικής και Ηθικής Θεωρίας, 2019)
The primary goal of the present research note is to concentrate on the electoral performance of far-right parties in the 2014 European Parliamentary elections in order to interpret the aspects of this vote through the bidirectional relationship between the demand and supply-side theory. According to the demand-side perspective, we discuss to what extent a range of socioeconomic issues affected the electoral dynamic of the far-right parties in the latest European elections. Simultaneously, our research purpose concentrates on the external supply-side developments referring to how the positions of mainstream parties across several ideological aspects and the subsequent configuration of party competition create electoral opportunities for the far-right parties. More specifically, by comparing the views of the electorally major centre-right, centre-left and far right parties across the dimensions of immigration and redistribution of the wealth, we ascertain how the configuration of party competition influences the electoral decision of voters towards the right-wing family. Therefore, the analysis provides comparative results according to which we deduce inferences regarding the overall presence of the far-right spectrum along the party systems of every single EU member-state.